Tackling antimicrobial resistance in Bangladesh: A scoping review of policy and practice in human, animal and environment sectors - Hoque, Roksana (PLoS One, 2020)
BACKGROUND: Antimicrobial resistance (AMR) has become an emerging issue in the developing countries as well as in Bangladesh. AMR is aggravated by irrational use of antimicrobials in a largely unregulated pluralistic health system. This review presents a ‘snap shot’ of the current situation including existing policies and practices to address AMR, and the challenges and barriers associated with their implementation. METHODS: A systematic approach was adopted for identifying, screening, and selecting relevant literature on AMR situation in Bangladesh. We used Google Scholar, Pubmed, and Biomed Central databases for searching peer-reviewed literature in human, animal and environment sectors during January 2010-August 2019, and Google for grey materials from the institutional and journal websites. Two members of the study team independently reviewed these documents for inclusion in the analysis. We used a ‘mixed studies review’ method for synthesizing evidences from different studies. RESULT: Of the final 47 articles, 35 were primary research, nine laboratory-based research, two review papers and one situation analysis report. Nineteen articles on human health dealt with prescribing and/or use of antimicrobials, five on self-medication, two on non-compliance of dosage, and 10 on the sensitivity and resistance patterns of antibiotics. Four papers focused on the use of antimicrobials in food animals and seven on environmental contamination. Findings reveal widespread availability of antimicrobials without prescription in the country including rise in its irrational use across sectors and consequent contamination of environment and spread of resistance. The development and transmission of AMR is deep-rooted in various supply and demand side factors. Implementation of existing policies and strategies remains a challenge due to poor awareness, inadequate resources and absence of national surveillance. CONCLUSION: AMR is a multi-dimensional problem involving different sectors, disciplines and stakeholders requiring a One Health comprehensive approach for containment.